Adversity & triumph: a blueprint for dental students - Muhamad Halil, Mohd. Haikal (WhiteCoat Group Sdn. Bhd., 2025)
Dental education is widely recognised as one of the most demanding professional training pathways, characterised by intense academic pressure, clinical challenges, emotional strain, and high expectations of professional conduct. Adversity & Triumph: A Blueprint for Dental Students offers a reflective and practical guide grounded in real-world experiences within dental education.